Study of Bondura® expanding PIN system - Akhtar, Muhammad Maaz (Strojniški vestnik, 2021)
Bolted connections are widely used in parallel plates and flanged joints to axially lock using the preload generated by the tightening torque and to constrain radial movements of the flanges by the surface friction between mating surfaces. The surface friction depends on the micro-asperities of mating surfaces; under the influence of vibrations and other external radial loads, these asperities tend to deform over time, resulting in the failure of the connection. The Bondura expanding pin system presented in this article is an innovative axial and radial locking system, in which the failure of bolted connections due to radial movements is eliminated by relying on the mechanical strength of the pin system along with the surface friction. The present study describes an experimental design to verify the maximum possible preload on the axial-radial pin at different levels of applied torque. The article also provides a realistic comparison of the pin system with standard bolts in terms of handling axial and radial loads. With some alterations in the axial-radial pin system’s design, the joint’s capability to resist failure improved appreciably compared with the original design and standard bolts with higher preload. As a result, the estimated capability improvement of the joint against the connection failure due to the external radial load by the axial-radial pin is observed to be more than 200 % compared to standard bolts. Considering the pros and cons of both fasteners, i.e., axial-radial pin and standard bolts, a practical solution can be chosen in which both fasteners are used in a connection, and an optimized situation can be developed based on the working conditions.
Keywords: aksialno varovanje; axial locking; bolt preload; contact asperities; ekspanzijski element; expanding pin system; flanged connection; hrapavost stičnih ploskev; prednapetost; prirobnična zveza; radial locking; radialno varovanje; samoodvijanje; shear resistance; shrink fit; strižna nosilnost